Low-Temperature Reactive Sintered Porous Mg-Al-Zn Alloy Foams - Solomon-Oshioke Agbedor; Donghui Yang; Jianqing Chen; Lei Wang; Hong Wu (Metals, 2022)
By using carbamide granules as the space holder, Mg alloy foams with interconnected pore structures were synthesized by reactive sintering of a mixture of Mg, Al and Zn powders. The effect of Zn/Al on the microstructural evolution and compressive strength of porous Mg-9Al-xZn (x = 1, 5) alloy foams was investigated. The phase diagram simulation approach was used to determine the sintering temperature. The analysis results show that the formation of binary secondary phases or intermetallic compounds is a crucial factor in achieving bonding strength for the porous Mg alloy foams. The intermetallic compounds were formed by solid-state diffusion between the metal powder elements. Mg17Al12 intermetallics was the most stable compound formed in the cell walls of porous Mg alloy foams. The addition of Zn influences the solubility and stability of the intermetallic compound. Thermodynamic calculations show that Mg17Al12 was preferentially formed in the cell walls owing to its high negative enthalpy energy. Moreover, various metastable transition phases may exist in the microstructures, especially in the porous Mg-9Al-5Zn alloy foam. The intermetallic phases act as reinforcing phases, combined with grain refinement, significantly increasing the strength of the foam. At the given relative density of 0.42, the porous Mg-9Al-5Zn alloy foam exhibits the highest yield strength of 9.0 MPa, which is 23% higher than the strength of the porous Mg-9Al-1Zn alloy foam.